Studies on characterization of nano CaCO3 prepared by the in situ deposition technique and its application in PP-nano CaCO3 composites - Mishra, Satyendra; Sonawane, S. H.; Singh, R. P. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The elegant approach of in situ deposition technique was used for the synthesis of nano CaCO3 the nanosize of particles was confirmed by the X-ray diffraction (XRD) technique. Differential scanning calorimetry (DSC) was used for determination of the enthalpy. The nano CaCO3 polypropylene (PP) composites were prepared by taking 2 and 10 wt % of different nanosizes (21-39 nm) of CaCO3. Conversion of the alpha phase to beta was observed in the case of 2 wt % of a 30-nm sized amount of CaCO3 in a PP composite. The decrement in DeltaH and percent. crystallinity, as well as the increment in melt temperature were recorded for 6 wt % nano CaCO3 with a decrease in nanosize from 39 to 21 nm. The increment in tensile strength with an increase in the amount of nano CaCO3 was observed, and the tower particle size shoved Greater improvement. The improvement in thermal and mechanical properties is because of the formation of a greater number of small spherulites uniformly present in the PP matrix. (C) 2004 Wiley Periodicals, Inc.
Keywords: Crystallization; DSC; mechanical and thermal properties; nano CaCO3; polypropylene; XRD

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties